SAT0500 Myocardial involvement at magnetic resonance in patients with systemic sclerosis and minor arrhythmias: association with clinical features and impact of treatment. (12th June 2018) - De Santis, M.; Monti, L.; Briani, M.; Indolfi, E.; Generali, E.; Isailovic, N.; Ceribelli, A.; Guidelli, G.M.; Caprioli, M.; Meroni, M.; Selmi, C.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune fibrotic disease characterised by variable clinical manifestations based on the predominant organ involvement. With the exceptions of acute fulminant myocarditis with pericardial effusion and heart failure, myocardial involvement in SSc is clinically silent until arrhythmias appear, while representing the major cause of sudden death or atrio-ventricular (AV) blocks in SSc. There are no reliable screening algorithm to discriminate myocardial involvement nor established treatments. Objectives: To identify early/clinically silent myocardial involvement in SSc and define a possible treatment. Methods: We used Holter electrocardiography (ECG) to investigate our cohort of patients with SSc (n=221, all fulfilling the ACR classification criteria) for ventricular ectopic beats (VEB)/AV blocks/unexplained tachycardia as sensitive signs of myocardial involvement. In 24 patients (women 23%–95.8%, anti-centromere-ACA 16%–66.6%, anti-topoisomerase-aScl70 3%–12.5%, anti-RNA polimerase III 3%–12.5%, anti-Ku 2%–8.3%, limited skin disease-lSSc 12%–50%, diffuse skin disease 5%–20.8%, sine scleroderma 7%–29.2%, median age 66.5 years, IQR 57.8–72.5), never treated with anti-fibrotic agents, we performed heart magnetic resonance (hMR) searching for myocardial oedema (on T2 STIR sequences, using the signal ratio between myocardium and skeletal muscle with a cut-off value of ≥1.9 for oedema) or fibrosis (presence of any late gadolinium enhancement (LGE) with intramyocardial or subepicardial pattern). Patients with myocardial oedema at hMR were treated with mycophenolate mofetil (MFM) 2 g/day or with azathioprine (AZA) 100 mg/day and underwent a control hMR after six months. Results: In 10/24 (42%) of the SSc cases with Holter ECG alterations (8 VEB, 1 tachycardia, 1 type II AV block) we observed SSc myocardial involvement at hMR. In more detail, 6 patients had myocardial oedema at T2 STIR sequences (including cases as follows: 1 aScl70-positive with lSSc and lung fibrosis, 2 ACA-positive with lSSc, 3 ACA-positive sine scleroderma ), and 4 only fibrosis (1 Scl70-positive with lSSc and lung fibrosis, 1 ACA-positive with lSSc, 1 ACA-positive sine scleroderma, 1 anti-Ku-positive sine scleroderma ). At 6 months of medical treatment, myocardial oedema disappeared in 3 patients treated with Aza and in 1 treated with MFM, the additional 2 patients are still receiving MFM treatment at the time of analysis. Conclusions: We observed that 42% of patients with SSc and minor arrhythmias on 24 hour Holter ECG have clinically silent myocardial involvement at hMR; those with potential reversible disease (oedema rather than fibrosis) favourably respond to immunosuppressants. Detectable serum ACA and the absence of skin involvement are over-represented in this subgroup of patients. Disclosure of Interest: None declared